Challenges and opportunities for technology transfer networks in the context of open innovation: Russian experience - Nadezhda Shmeleva; Leyla Ayvarovna Gamidullaeva; Tatyana Olegovna Tolstykh; Denis Lazarenko (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Nowadays, the relevance of technology transfer center network has been greatly increased due to interdisciplinary modern innovations, and cross-sectoral collaboration in project implementation. This paper highlights theoretical and conceptual foundations of technology transfer, and the role of innovation and knowledge. The main purpose of the paper is to analyze the experience of creating technology transfer networks in Russia, and to develop prospective national technology transfer model based on the concept of innovation ecosystem and open innovation. Being a knowledge integrator, a university plays a vital role in technology transfer. The presented study makes contribution to the academic literature by providing a synthesis on related concepts of open innovation, network, and ecosystem approaches to technology transfer. The results of this analysis provide information on prospective models for creating a network of technology transfer in Russia. That will help academics, policymakers, government, and business owners with a more depth understanding of the practical mechanisms that support innovation strategy.
Keywords: 650; clusters; cross-sectoral collaboration; innovation ecosystem; network models; open innovation; technological cooperation; technology transfer